The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13640-016-0155-0
|View full text |Cite
|
Sign up to set email alerts
|

High payload secret hiding technology for QR codes

Abstract: Quick response (QR) code has become one of the more popular two-dimensional barcodes because of its greater data capacity and higher damage resistance. The barcode scanners can easily extract the information hidden in the QR code while scanning the data modules. However, some sensitive data directly stored in QR codes are insecure in real-world QR applications, such as the e-ticket and e-coupon. To protect the sensitive data, this paper explores the characteristics of QR barcodes to design a secret hiding mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 12 publications
0
46
0
2
Order By: Relevance
“…Taking (7,4) Hamming code for example, we explain how to embed and extract 3 bits of messages into 7 pixels. Let H be the parity check matrix of the (7,4) Hamming code whose columns are in the natural order of increasing binary numbers.…”
Section: Methods Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking (7,4) Hamming code for example, we explain how to embed and extract 3 bits of messages into 7 pixels. Let H be the parity check matrix of the (7,4) Hamming code whose columns are in the natural order of increasing binary numbers.…”
Section: Methods Ofmentioning
confidence: 99%
“…Based on the error correction mechanism of QR code, Chiang et al [6] used wet paper code to embed secret information into the carrier image to achieve blind extraction of secret information. Lin and Chen [7] improved the algorithm to make the upper limit of the embedded bits reach the maximum data capacity of the QR code. Lin [8] proposed a (n, n) secret sharing scheme where n bit streams were obtained by the random number generation algorithm and hash function and embedded into the carrier image by wet paper code to form n two-level QR codes.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations demonstrated that the scheme has low computational complexity but no error-correction ability; when any bit of the carrier QR barcode is damaged, it is difficult to recover the secret payload. Lin et al [15] improved the steganography scheme of Reference [13] and used the concept of the exploiting modification direction (EMD) scheme to hide secret payloads in QR barcodes. Compared with Reference [13], Reference [15] improved the hiding capacity, and the secret payload could be recovered with few errors.…”
Section: Related Workmentioning
confidence: 99%
“…Some existing digital steganography schemes [4,[9][10][11][12] do not work properly in this scenario because the hidden data are destroyed. Other steganography schemes [13][14][15] based on QR barcodes are not easy to use in the real world because they are not robust to complex physical factors.…”
Section: Introductionmentioning
confidence: 99%
“…Quick response (QR) code has become one of the more popular two-dimensional barcodes due to its inherent data capacity and higher damage resistance [1]. With smartphone security and privacy becoming a major concern [2], a hijacked QR code can be a dangerous attack vector for smartphone users.…”
Section: Introductionmentioning
confidence: 99%